New Relation between the Coefficients of a Rational Function and the intersection points with Oblique Asymptotes in a Vector Equations (Sulaimani Journal for Pure and Applied Sciences, 2021)
It’s clear that Vieta’s formula relates the coefficients of polynomial to the sum and product of their roots. In this paper for the first time, we introduce a vector equations relate the coefficients of numerator and denominator of rational functions to the sum and product of intersection points with oblique asymptotes. Furthermore, previously we learned how to find Oblique asymptote of rational functions by Long division, but in this paper we introduce new easier method for finding oblique asymptotes of rational functions with the aid of determinant of a matrix.
Keywords: Vieta’s Formula; Vector Equation; Rational Function; Asymptotes; Oblique Asymptote; Slant Asymptote